2016
DOI: 10.5152/ucd.2016.3285
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of childhood burns and parental awareness in Turkey

Abstract: Objective: Burns continue to be a devastating trauma worldwide. Most of the childhood burns are due to preventable injuries. Burns occurring as a result of negligence of the parents'/carers' may cause mortality or life-long morbidities. Identification of the etiologies will direct the precautions that should be undertaken. Material and Methods:One hundred consequent burn patients admitted to our clinics were included to the study. A questionnaire was filled in with the information gathered from the parents/car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 12 publications
6
20
0
Order By: Relevance
“…Burn injuries may vary depending on the socio-cultural and socio-economic status of the country in question although burn injuries are more common in male children under the age of four in all communities. 1 , 2 , 4 , 6 Similarly, in our study, burn injuries were found to be common particularly in male children aged 2–4 years although no statistically significant difference was found in terms of age and sex (p> 0.05).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Burn injuries may vary depending on the socio-cultural and socio-economic status of the country in question although burn injuries are more common in male children under the age of four in all communities. 1 , 2 , 4 , 6 Similarly, in our study, burn injuries were found to be common particularly in male children aged 2–4 years although no statistically significant difference was found in terms of age and sex (p> 0.05).…”
Section: Discussionsupporting
confidence: 64%
“…Burn injuries are more commonly seen in undeveloped societies where there is a low socio-economic status, and mostly in rural areas. 1 , 2 In the United States, burns are one of the most common causes of mortality and morbidity among children 3 Children are at greater risk since their defense mechanisms and reflexes are not fully developed. 4 …”
Section: Introductionmentioning
confidence: 99%
“…There was a statistically significant association between affected TBSA and mortality (p= 0.001). There is a consensus in the literature that larger affected TBSA is associated with a high mortality rate (11)(12)(13). A recent study reported that affected TBSA over 40% is a risk factor for mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Antibiotics should not be used for prophylaxis in burn, because it is well known that prophylactic antibiotic usage leads to colonization of resistant strains. [12] In cases where sepsis is strongly suspected, the initial antibiotic regimen to be delivered until the laboratory results are obtained should cover these organisms.…”
Section: Discussionmentioning
confidence: 99%